Cohesive Ties Found in Writing English Text at SMA Dharma Wanita 2023/2024 Medan - Karisma Erikson Tarigan; Meikardo Samuel Prayuda; Rosma Sani Fitria br Sinukaban (Journal of English Language Learning, 2023)
Cohesive is a concept applied to text linguistics and discourse analysis to determine if the written text's properties. Cohesive ties are divided into five categories: reference, substitution, ellipsis, conjunction and lexical ties. This research was conducted to look at the types of lexical cohesive ties in student description writing and the dominant cohesive ties found in the writing of SMA Dharma Wanita students. This research is limited by two types of cohesive ties, namely reference and conjunction. This study used the qualitative data techniques. Based on the results of student writing through descriptive text, there were 114 cohesive ties used by students with 32 cohesive tie reference types and 82 conjunctions.